Proposta participativa de redesenho agroecológico da microbacia do Córrego Três Barras - Coletty, Carlos Eduardo (Universidade Federal de São Carlos, 2009)
The exploration of the extensive livestock and of the coffee s monoculture, nowadays abandoned, associated with the abandonment of traditional cultures led to the degradation of the micro watershed of the Córrego Três Barras at the city of Jacutinga, south of Minas Gerais. For not get the culture of their lands sustenance local agricultural families seek for work in neighboring cities. This reality motivated the search for alternatives that can contribute to ambient, economic and social recovery in this region. The general goal of this work was to established, in a participatory manner, the bases in which this community can redraw their model of occupation through an adoption of agroecological concepts and practices. The specific goal was to indentify the potentialities and the critical aspects through the realization of a Rural Participatory Diagnosis DRP. This case study was made in the farm/site Três Barras, property that features the rural familiar agricultural of the others properties of this agroecosystem. The comprehension/understanding of this diagnosis allowed to the local social actors the beginning of a new development´s draw with the agroecological practices adoption.
Keywords: Agroecologia; Sustentabilidade; Metodologias participativas; CIENCIAS AGRARIAS